2017
DOI: 10.12816/0038206
|View full text |Cite
|
Sign up to set email alerts
|

Placental Cord Drainage versus No Placental Drainage in the Management of Third Stage of Labour : Randomized Controlled Trial

Abstract: Back ground:the third stage of labour begins immediately after the birth of the baby and ends with the expulsion of the placenta and fetal membranes.It is preceded by contraction and retraction of the uterus to reduce uterine size and expel the placenta with minimal haemorrhage. Placental cord drainage involves clamping and cutting of the umbilical cord after the birth of a baby and then, immediately unclamping the maternal side of the cord so the blood can drain freely into a container. Aim of the work:the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
(5 reference statements)
3
5
0
Order By: Relevance
“…The current study results revealed that there were significant differences were observed between the PCD and control group in relation to the manual removal of placenta, need for blood transfusion, and uterine condition during postpartum period. These findings are partially in the same line with the previously mentioned studies conducted by Mithala et al, [23] and Mohamed et al, [24] they reported that the retained placenta was less frequent among PCD group than control. They further added that the need for postpartum blood transfusion was lower in PCD group compared to control without significant differences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The current study results revealed that there were significant differences were observed between the PCD and control group in relation to the manual removal of placenta, need for blood transfusion, and uterine condition during postpartum period. These findings are partially in the same line with the previously mentioned studies conducted by Mithala et al, [23] and Mohamed et al, [24] they reported that the retained placenta was less frequent among PCD group than control. They further added that the need for postpartum blood transfusion was lower in PCD group compared to control without significant differences.…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that there were significant difference between both groups regarding postpartum systolic BP, diastolic BP and pulse. This result is congruent with the previously mentioned study conducted by Mohamed et al, [24]. They concluded that the postpartum systolic blood pressure, diastolic blood pressure and pulse were affected among PCD group compared to control.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…They reported significance difference in postpartum haemoglobin level in placental cord drainage group than control group. 6,9,[12][13][14] There were certain limitations in our study. Sample size being 50 in study group so the results cannot be generalised.…”
Section: Discussionmentioning
confidence: 99%